Neurocognitive disorders in young adults commencing highly active antiretroviral treatment in the Western Cape - Joska, John Anton (Department of Psychiatry and Mental Health, 2025)
Background: HIV-associated neurocognitive disorders (HAND) remain prevalent in the era of highly active anti-retroviral therapy (HAART). It is not known whether HAND are as prevalent in South Africa as in other regions, and whether individuals with HAND in South Africa will respond to HAART. Methods: The published literature was reviewed to elucidate potential mechanisms of the development of HIV-associated dementia (HAD)- the most severe form of HAND- and to establish the effect that HAART has exerted on HAND across diverse studies. A prospective clinical cohort study was initiated in Cape Town, in which 170 participants completed baseline clinical and neuropsychological assessments. Laboratory investigations included apolipoprotein E (APOE) genotyping. The performance of the International HIV Dementia Scale (IHDS) as a brief screening tool was analysed using a receiver operating characteristic (ROC). At one-year, 105 participants were re-assessed for neuropsychological change. Results: The reviewed literature suggests that HAD is likely mediated by a range of HIV-related factors (including possible difference in HIV sub-type) and host-related factors. In addition, while neurocognitive improvements are reported in most prospective studies, these are dogged by differences in methodology and approach. In this study, 25.4% of participants met criteria for HAD at baseline and this was associated with lower levels of education and male gender. The APOE4 allelic variant was not associated with those who had developed HAD, despite this variant being common in Cape Town. The IHDS performed reasonably well on ROC analysis, detecting 86% of dementia cases using a cut-off score of ≤11. At one-year follow-up, participants had improved significantly on neuropsychological assessment, including a small sub-sample who had not initiated HAART. Significant associated factors were male gender, the use of HAART and worse baseline neuropsychological test performance. Conclusion: HAND- including HAD- are common conditions in South Africa, where HIV clade C is predominant. Further work to identify cases and delineate mechanisms of disease and treatment response is needed. This might take the form of larger prospective studies, incorporating control groups. Such studies could better elucidate disease mechanisms with a view to developing targets for therapeutic interventions.